The assessment and treatment of older adults the watch and wait holistic model - Hyer, Lee (Cambridge Scholars Publishing, 2020)
This book is intended for health care professionals, as well as academics who work with this population. It articulates a watch and wait model of care, with five domains presented as a sufficient understanding of a case: general health, cognition, depression, anxiety, and life adjustment.